Pengaruh Sales Promotion, Kemudahan, dan Kepuasan terhadap Sikap Konsumen Pengguna Aplikasi E-Wallet Gopay (Studi Kasus pada Mahasiswa Universitas Muhammadiyah Bengkulu) - Fadhilah Akbar; Islamuddin Islamuddin; Yosa Ika Sari; Eka Setiawati (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research aims to determine the effect of promotion, convenience and satisfaction on consumer attitudes when using the Go-pay e-wallet application (case study of Bengkulu Muhammadiyah University students). . This type of research uses a quantitative descriptive method. The population used in this study were students at the University of Muhammadiyah Bengkulu. The number of respondents in this study were 130 people. The collected data was processed using classical hypothesis testing techniques, multiple linear regression analysis techniques, analysis of the coefficient of determination (R2), partial tests (T tests) and time homogeneity tests (F tests). The results of this research indicate that some promotional variables (X1) have a significant influence on the consumer attitude variable (Y), H1 is accepted. Convenience (X2) has a significant effect on the consumer attitude variable (Y), H2 is accepted, and satisfaction variable (X3) has a significant effect on the consumer attitude variable (Y), H3 is accepted. Meanwhile, the f test on promotion (X1), convenience (X2) and satisfaction (X3) has a significant influence on consumer attitudes (Y) in using the Gopay e-wallet application, so that H4 D is accepted. The overall significance level is 0.000 (<0.005). It also has a regression equation Y = 2.060 + 0.214 X1 + 0.286 X2 + 0.372 The coefficient of determination means that sales promotion, convenience and satisfaction together contribute primarily to consumer attitudes towards Go-pay e-wallet application users. And the variable with the most dominant regression coefficient value is the satisfaction variable (X3) with a value of 0.372.